Cockfighting in Costa Rican Written Press: A Critical Discourse Analysis of Some News in La Nación S.A. Newspaper - Rodríguez Aguilar, Onésimo (2014)
The following article arises from an ongoing research project, developed by the School of Anthropology -Escuela de Antropología- at La Universidad de Costa Rica, entitled "Good Cock dies!. Youngters, cockpits and cockfighting”. This text is the first part of such research and it is focused on analyzing the perspective of La Nación S.A. newspaper in relation to the cockfight phenomenon in Costa Rica. We used Critical Discourse Analysis, as a methodological tool, as it makes it possible to see ideas that seem to emerge from La Nacion, S.A. with the purpose of raising moral awareness within the readers by using discourse-evaluative strategies, addressed in a sensationalist and thoughtless manner. Thus, it is evident that this media requires this kind of approaches to show the violence of cockfighting, and to hide the violence committed by its way of exposing and analyzing the social dynamics.